2017
DOI: 10.1002/2017jd026880
|View full text |Cite
|
Sign up to set email alerts
|

A spatiotemporal analysis of the relationship between near‐surface air temperature and satellite land surface temperatures using 17 years of data from the ATSR series

Abstract: The relationship between satellite land surface temperature (LST) and ground‐based observations of 2 m air temperature (T2m) is characterized in space and time using >17 years of data. The analysis uses a new monthly LST climate data record (CDR) based on the Along‐Track Scanning Radiometer series, which has been produced within the European Space Agency GlobTemperature project (http://www.globtemperature.info/). Global LST‐T2m differences are analyzed with respect to location, land cover, vegetation fraction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
83
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(93 citation statements)
references
References 92 publications
(176 reference statements)
10
83
0
Order By: Relevance
“…Our result is also consistent with the study by Good et al (2017), who showed the stronger coupling between global surface and air temperature at their minima. They attributed the weaker daytime coupling of the two temperatures to the influence of insolation.…”
Section: Discussionsupporting
confidence: 94%
“…Our result is also consistent with the study by Good et al (2017), who showed the stronger coupling between global surface and air temperature at their minima. They attributed the weaker daytime coupling of the two temperatures to the influence of insolation.…”
Section: Discussionsupporting
confidence: 94%
“…Generally, the magnitude of nighttime T surf and T air is very close (differing by <5°C), regardless of land-cover type (Good et al 2017). Generally, the magnitude of nighttime T surf and T air is very close (differing by <5°C), regardless of land-cover type (Good et al 2017).…”
Section: Introductionmentioning
confidence: 96%
“…However, relationships among these factors are not straightforward (Good 2016, Good et al 2017, Jin and Dickinson 2010, Lee et al 2011, Mildrexler et al 2011. Differences between T surf and T air may be driven by land cover (especially, vegetation cover and surface roughness) and atmospheric properties (e.g., cloud cover, water vapor content, and surface boundary layer processes), in addition to factors such as soil moisture, elevation, net radiation, and latitude.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences between ATSR‐2 and AATSR in the Arctic is around 1 K (Ghent et al, ). Future work should include harmonization to reduce differences between the sensors, following studies such as Good et al (), Merchant et al (), and Merchant et al (). As noted in sections and , land sea masking and sea ice masking are different between the SST L2P and GT LST data sets providing the input T s for AAST.…”
Section: Discussionmentioning
confidence: 99%